Eye Movement Desensitisation and Reprocessing (EMDR) therapy for prolonged grief: theory, research, and practice - Spicer, Liam (Frontiers in Psychiatry, 2024)
Prolonged Grief Disorder occurs within 7-10% of the bereaved population and is a more complicated and persistent form of grief which has been associated with suicidality, mental health disorders, sleep disturbance, poor health behaviors, and work and social impairment. EMDR is a fitting treatment option for those with Prolonged Grief, focusing on processing past memories, blocks, current triggers, future fears, and preparing the person for living life beyond the loss in line with the Adaptive Information Processing Model and grief frameworks. This paper discusses the theory, research regarding the application of EMDR with prolonged grief, and gives insight and guidance to clinicians working in this area including a case example.